Responsive blends of block copolymers stabilize the hexagonally perforated lamellae morphology. Issue 14 (22nd March 2023) - Nowak, Samantha R.; Tiwale, Nikhil; Doerk, Gregory S.; Nam, Chang-Yong; Black, Charles T.; Yager, Kevin G.
Abstract : Blends of block copolymers are responsive materials that can form phases distinct from the constituent materials. Abstract : Blends of block copolymers can form phases and exhibit features distinct from the constituent materials. We study thin film blends of cylinder-forming and lamellar-forming block copolymers across a range of substrate surface energies. Blend materials are responsive to interfacial energy, allowing selection of pure or coexisting phases based on surface chemistry. Blending stabilizes certain motifs that are typically metastable, and can be used to generate pure hexagonally perforated lamellar thin films across a range of film thicknesses and surface energies. This tolerant behavior is ascribed to the ability of blend materials to redistribute chains to stabilize otherwise high-energy defect structures. The blend responsiveness allows the morphology to be spatially defined through multi-tone chemical surface patterns.